History of Chemical Routes towards Cyclic Non-Enzymatic Oxygenated Metabolites of Polyunsaturated Fatty Acids - Oger, Camille; Cuyamendous, Claire; de la Torre, Aurélien; Candy, Mathieu; Guy, Alexandre; Bultel-Poncé, Valérie; Durand, Thierry; Galano, Jean-Marie (Synthesis, 2018)
Enzymatically formed oxygenated metabolites of polyunsaturated fatty acids (PUFA) are of great interest for the scientific community being mediators and biomarkers in the physiological and pathological regulation of many key biological processes. More recently; metabolites of PUFA formed through a non-enzymatic free radical pathway have gained interest in diseases linked with oxidative stress. Thus, synthetic strategies leading to the total synthesis of such metabolites are an essential field of research, and this review will cover a structural presentation, will discuss their biological interests, and present total syntheses reported between 2008 and 2017.1 Introduction2 Non-Enzymatic Metabolites of PUFAs2.1 Where Do They Come From?2.2 Why Are They Interesting Metabolites?2.3 A Huge Family of Natural Compounds2.3.1 Presentation of All Families2.3.1.1 Isoprostanoids2.3.1.2 Isofuranoids2.3.1.3 Isoketals2.3.2 Nomenclature of These Metabolites2.3.2.1 Isoprostanoids2.3.2.2 Isofuranoids2.3.2.3 Isoketals3 Total Synthesis Strategies3.1 Isoprostanoids3.2 Isofuranoids3.3 Isoketals4 The Discoveries Behind the Synthesis4.1 Recent Identification and Biomarkers Roles of Isoprostanes and Isofuranes4.2 Biological Properties4.2.1 Phytoprostanes, Isoprostanes, and Neuroprostanes4.2.2 Epoxy-isoprostanes5 Conclusion
Keywords: total synthesis; lipids; isoprostanes